National Geographic United States atlas for young explorers. - National Geographic Society (U.S.) (Washington, D.C. : National Geographic, 2008)
Presents world, regional, and thematic maps as well as photographic essays on each state.
Front of the book -- Northeast -- Southeast -- Midwest -- southwest -- West -- Territories -- Back of the book.
Previous ed.: 2004.
Includes index.
Keywords: United States -- Maps; Children's atlases; Atlases; Children's atlases; United States; Maps; Children's maps